Association between vitamin D receptor polymorphisms (BsmI and FokI) and glycemic control among aatients with type 2 diabetes - Zakaria, Wan Nur Amalina; Mohd Yunus, Nazihah; Yaacob, Najib Majdi; Omar, Julia; Wan Mohamed, Wan Mohd Izani; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Tuan Ismail, Tuan Salwani (MDPI, 2021)
Background: Several studies have suggested that the vitamin D receptor (VDR) gene plays a role in type 2 diabetes mellitus (T2DM) susceptibility. Nonetheless, the association between T2DM and VDR polymorphisms remains inconclusive. We determined the genotype of VDR rs1544410 (BsmI) and rs2228570 (FokI) polymorphisms among Malaysian patients with T2DM and their association with glycemic control factors (vitamin D levels, calcium, magnesium, and phosphate). (2) Methods: A total of 189 participants comprising 126 patients with T2DM (63 with good glycemic control and 63 with poor glycemic control) and 63 healthy controls were enrolled in this case–control study. All biochemical assays were measured using spectrophotometric analysis. VDR gene FokI and BsmI polymorphisms were analyzed using polymerase chain reaction and endonuclease digestion. (3) Results: Our findings revealed no significant differences in VDR FokI and BsmI genotypes between participants with T2DM and healthy controls. Moreover, no significant association was observed between both single nucleotide polymorphisms and glycemic control factors. Participants with poor glycemic control had significantly lower serum magnesium levels and significantly higher HOMA-IR compared to the other groups. (4) Conclusions: The present study revealed that VDR gene BsmI and FokI polymorphisms were not significantly associated with T2DM.